Modeling the sampling volume for the skin blood oxygenation measurements - Meglinski, I. V.; Matcher, S. J. (Springer Science Business Media, 2001)
Abstract The absolute quantified measurement of haemoglobin skin blood saturation from collected reflectance spectra of the skin is complicated by the fact that the blood content of tissues can vary both in the spatial distribution and in the amount. These measurements require an understanding of which vascular bed is primarily responsible for the detected signal. Knowing the spatial detector depth sensitivity makes it possible to find the best range of different probe geometries for the measurements of signal from the required zones and group of vessels inside the skin. To facilitate this, a Monte Carlo simulation has been developed to estimate the sampling volume offered by fibre-optic probes with a small source-detector spacing (in the current report 250 μm, 400 μm and 800 μm). The optical properties of the modelled medium are taken to be the optical properties of the Caucasian type of skin tissue in the visible range of the spectrum. It is shown that, for a small source-detector separation (800 μm and smaller), rough boundaries between layers of different refractive index can play a significant role in skin optics. Wavy layer interfaces produce a deeper and more homogeneous distribution of photons within the skin and tend to suppress the direct channelling of photons from source to detector. The model predicts that a probe spacing of 250 μm samples primarily epidermal layers and papillary dermis, whereas spacings of 400–800 μm sample upper blood net dermis and
Keywords: Sampling volume; Light scattering; Human skin; Monte Carlo simulation; Skin blood oxygenation; Multi-layered media